Cementless hemispheric acetabular components: 2–4-year results - Incavo, Stephen J.; DiFazio, Frank A.; Howe, James G. (The Journal of arthroplasty, 1993)
A retrospective clinical and radiographic analysis was performed on 99 patients (106 hips) undergoing total hip arthroplasty with noncemented Harris-Galante (Zimmer, Warsaw, IN) or Optifix (Smith Nephew Richards, Memphis, TN) acetabular components. There were 94 primary and 12 revision procedures with a minimum follow-up period of 24 months (range, 24–52 months). The cups were evaluated for evidence of vertical and horizontal migration, as well as the presence of radiolucencies at the bone-implant interface. Age, sex, component inclination and medialization, cup coverage, and number of fixation screws used were examined to determine the influence of these factors on the incidence of cup migration or radiolucent line formation. A radiolucent line was present in at least one zone in 60% of the Harris-Galante and 45% of the Optifix cups. Progressive radiolucent lines were noted in two of the Optifix and three of the Harris-Galante components. Two Harris-Galante cups (1.9%) were revised. There were no Optifix cup migrations or evidence of instability in the Optifix or remaining Harris-Galante cups. Although there was a trend toward an increased incidence of radiolucencies in those cups lacking complete coverage, no statistically significant radiographic predictors for failure or impending failure could be determined from this short-term follow-up study. With the exception of the two revisions, all acetabular components performed well clinically over the study period.